History Off-Hand: Bunnell's No-Man's Land. (July 2019) - Hage, J. Joris
Background: To date, it remains unclear what inspired Dr Sterling Bunnell to start using the typical World War I military term no-man's land in hand surgical context, only in 1948. To commemorate that Bunnell passed away 60 years ago on August 20, I report on my quest to clarify this.Methods: An extensive bibliography of Bunnell was made up by use of the McDowell Series of Plastic Surgery Indexes and cross-checked by use of a PubMed search. Bunnell's round-robin letters were searched for in the Sterling Bunnell Hand Surgery Archives of the California Pacific Medical Center Health Services Library in San Francisco, California. In addition, some of the second-generation hand surgeons were personally approached to try and trace the round-robin letters . Finally, the publications of the chiefs of the 9 hand surgical centers and 6 coworkers of Bunnell were checked for referrals to the term no-man's land .Results: Prior to 1948, no-man's land was not used in print in hand surgical context. Bunnell's nearness to the trenches during World War I appears not to have inspired him immediately to start using the term. The reconnaissance tunnels dug through the soil of the no man's land between the Allied and German trenches likely inspired him to replace a cut tendon through incisions proximal and distal to no-man's land .Conclusions: Bunnell must have associated his tendon grafting techniques to that of the World War I trenches and tunnels at some time between 1947 and 1948.